2018
DOI: 10.3389/fmicb.2018.02912
|View full text |Cite
|
Sign up to set email alerts
|

Regulation of Monospecies and Mixed Biofilms Formation of Skin Staphylococcus aureus and Cutibacterium acnes by Human Natriuretic Peptides

Abstract: Staphylococcus aureus and Cutibacterium acnes are common representatives of the human skin microbiome. However, when these bacteria are organized in biofilm, they could be involved in several skin disorders such as acne or psoriasis. They inhabit in hollows of hair follicles and skin glands, where they form biofilms. There, they are continuously exposed to human hormones, including human natriuretic peptides (NUPs). We first observed that the atrial natriuretic peptide (ANP) and the C-type natriuretic peptide … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
45
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 32 publications
(48 citation statements)
references
References 57 publications
2
45
1
Order By: Relevance
“…2, 3). The minimum biofilm thickness recorded in this study (160 ± 37 μm) was higher than the 30 ± 2 μm thickness recorded for S. aureus MFP03 34 . In this study, the formation of thicker biofilms by the S. aureus Newman strain compared to literature may be partly due to stronger adhesion under the dynamic conditions employed in our biofilm assay 35 .…”
Section: Discussioncontrasting
confidence: 78%
“…2, 3). The minimum biofilm thickness recorded in this study (160 ± 37 μm) was higher than the 30 ± 2 μm thickness recorded for S. aureus MFP03 34 . In this study, the formation of thicker biofilms by the S. aureus Newman strain compared to literature may be partly due to stronger adhesion under the dynamic conditions employed in our biofilm assay 35 .…”
Section: Discussioncontrasting
confidence: 78%
“…However, bioinformatic studies performed on the sequenced genome of C acnes revealed the presence of an amidase showing 69% homology with the P aeruginosa AmiC protein previously identified as the sensor for CNP in this bacterium. [63] No protein ortholog to the human natriuretic peptide receptor (NPR-C) was found in the genome of S aureus but this bacterial species also express enzymes showing partial homology with the bacterial sensor for CNP, AmiC. [63] Therefore, as SP and CGRP, in skin, natriuretic peptides should also regulate the behaviour of cutaneous bacteria, but through an original way involving a mechanism dependent of the temperature.…”
Section: Natriuretic Peptidesmentioning
confidence: 99%
“…Skin thus may be a target, as well as an active element, in the hypothalamic-pituitary-adrenocortical axis activated during stress (16). It has been recently demonstrated that cutaneous bacteria, including Staphylococcus aureus, Staphylococcus epidermidis, Pseudomonas fluorescens, Bacillus cereus , and Cutibacterium (former Propionibacterium ) acnes can sense and react to skin neuropeptides, such as substance P, calcitonin gene related peptide, and natriuretic peptides (1720). Thus, the skin microbiota may be a relay in neurogenic inflammation (21).…”
Section: Introductionmentioning
confidence: 99%